RESPONSIBILITY PRODUCER CONCERNING GIVING LEGAL FOODS PRODUCT CONSUMER PROTECTION LAW PERSPECTIVE - ., Kurniawan; Sutrisno, Budi; Martini, Dwi (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Problem of label foods product very important because a part consumer is in muslim circle whereas in statistics more than 80% Indonesian occupation is Islam religion Consume activity certain of material foods for muslim it just not only for fulfill hungry but more than worship to God. For ensure the permitted of product then by producer, that product must imploring certification of permitted before marketing for muslim consumer. For every produser going to having include label product in their product it must following process or stage to get permitted instruction consist of pre registration and registration up to publication of permitted certificate graduated by MUI after permanently of permitted status by instruction commision of MUI. Consequences law for producer carry out inclusion of permitted label of product illegal from clause of UU Consumer Protection although UU No. 7 years 1996 about Label and Foods and PP No 69 years 1999 about Label and Foods Advertising there are three categories, producer can be allowed acted crime, civil although administratif. Besides that consequences law for producer that include permitted label of foods roduct, illegal actually really adverse the muslim consumer is like responsibility from producer to consumer, in other wise responsibility of producer like product responsibility it means responsibility product for that product bring along in currency that have made or included loss because flawed at that product.